7 Views of future care planning in patients aged over 70 years old and carers: developing a strategy for qualitative research through co-design. Issue 3 (1st September 2017) - Bielinska, Anna-Maria; Archer, Stephanie; Riley, Julia; Urch, Catherine
Abstract : Introduction: Following an emergency hospital admission in over 70-year-olds, 1 year mortality is approximately 20%, highlighting the need for future care planning (FCP) (Bielinska, 2016). Conducting research around FCP with patients and carers is an emotive topic; co-designing a research strategy may lead to more acceptable, in-depth interviews. (Borgstrom, 2017). Aim: To co-design a qualitative research strategy to explore views on FCP in patients over 70 and carers. Methods: A research collaborative co-designed a qualitative study exploring patient-led FCP for emergency admissions in patients aged 70+years, inclusive of all diagnoses. The research collaborative particularly focused on the co-design of a semi-structured interview schedule and associated linguistic content. Results: Outputs from iterative reflections with palliative care clinicians and a patient and carer group were incorporated to produce themes for the semi-structured interview. Co-designed themes: 1) an acceptable approach to FCP, including timing and terminology 2) significance of FCP as perceived benefits or harms 3) expectations of the content of FCP 4) expectations of whether to share FCP with medical or social contacts Areas of difference: 1) direct questioning for resuscitation orders 2) need for formal assessment scales Conclusions: Understanding FCP in the 70 years+cohort is important for individualised care; interview co-design can enable sensitive exploration. An iterative methodology can be useful for co-designing a semi-structured interview schedule Co-design allows for differences between patient and healthcare perspectives to be reconciled, resulting in the development of a robust and acceptable tool for research. References: 1. Bielinska A, Obanobi A, Riley J, Urch CE. One year mortality: recognising the need for urgent or advance care planning in adults aged over 70 years old following emergency admission. BMJ Supportive & Palliative Care2016;6:385. 2. Borgstrom E, Barclay S. Experience-based design, co-design and experience-based co-design in palliative and end-of-life care. BMJ Support Palliat Care2017;Published Online First: 16 February 2017. doi: 10.1136/bmjspcare-2016-001117